EFFICIENCY OF COMPOST PRODUCTION IN SIDODADI VILLAGE: THE ROLE OF ORGANIC WASTE CHOPPER MACHINE TECHNOLOGY - Mindarta, Erwin Komara; Wulandari, Retno; Komarudin, Komarudin; Romadhon, Afif Rizqi Nizar; Susilo, Eko; Effendi, Muhammad Idris; Setiawan, Rama Adi; Thoriq, Muhammad Syiva (Jurnal Dinamika Vokasional Teknik Mesin, 2024)
The size of organic waste affect the compost production process efficiency. There is a need to develop the chopper machine to chop the organic waste into smaller size. This study evaluates the application of Organic Waste Chopper Machine technology to improve the efficiency of the compost production process in Sidodadi Village, Ngantang District, Malang Regency. The results of the study indicate that the use of this organic waste chopper machine significantly increases the volume of compost production, shortens the composting time, and produces compost with higher nutritional quality. In addition, this technology also successfully reduces unprocessed organic waste, thus contributing positively to the environment and reducing production costs for the village community. Although this technology is effective, challenges in terms of access to spare parts and financing remain. Therefore, continued support from the government, technical training, and collaboration with educational institutions are needed to ensure the sustainability and further development of this program.